Machining feature-based system for supporting step-compliant milling process - Chen, Wong Keong (2018)
STEP standards aims at setting up a standard description method for product data and providing a neutral exchanging mechanism that is independent of all the information processing systems for product information model. STEP Part 21 is the first implementation method from EXPRESS language and implemented successfully in CAD data. However, this text file consists of purely geometrical and topological data is hardly to be applied in machining process planning which requires machining features enriched data. The aim of this research is developing a new methodology to translate the EXPRESS language model of CAD STEP data into a new product data representation and enriched in machining features which is more beneficial to machining process planning. In this research, a target Database Management System (DBMS) was proposed for developing this system by using its fourth-generation tools that allow rapid development of applications through the provision of nonprocedural query language, reports generators, form generators, graphics generators, and application generators. The use of fourth-generation tools can improve productivity significantly and produce program that are easier to maintain. From this research, a new product data representation in a compact new table format is generated. Then this new product data representation has gone through a series of data enrichment process, such as normal face direction generation, edge convexity/concavity determination and machining features with transition feature recognition. Lastly, this new enriched product data representation is verified by generating to a new STEP standard data format which is according to ISO1030-224 standard format and providing an important part of solution for supporting STEP-compliant process planning and applications in milling process.